Nitrogen dioxide (NO2) uptake by vegetation controlled by atmospheric concentrations and plant stomatal aperture - Chaparro-Suarez, I. G.; Meixner, F. X.; Kesselmeier, J. (Atmospheric Environment, 2011)
Nitrogen dioxide (NO2) exchange between the atmosphere and ﬁve European tree species was investigated in the laboratory using a dynamic branch enclosure system (consisting of two cuvettes) and a highly speciﬁc NO2 analyzer. NO2 measurements were performed with a sensitive gas phase chemiluminescence NO detector combined with a NO2 speciﬁc (photolytic) converter, both from Eco-Physics (Switzerland). This highly speciﬁc detection system excluded bias from other nitrogen compounds. Investigations were performed at two light intensities (Photosynthetic Active Radiation, PAR, 450 and 900 mmol m2 s 1 ) and NO2 concentrations between 0 and 5 ppb. Ambient parameters (air temperature and relative humidity) were held constant. The data showed dominant NO2 uptake by the respective tree species under all conditions. The results did not conﬁrm the existence of a compensation point within a 95% conﬁdence level, though we cannot completely exclude emission of NO2 under very low atmospheric concentrations. Induced stomatal stricture, or total closure, by changing light conditions, as well as by application of the plant hormone ABA (Abscisic Acid) caused a corresponding decrease of NO2 uptake. No loss of NO2 to plant surfaces was observed under stomatal closure and species dependent differences in uptake rates could be clearly related to stomatal behavior
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Deposition; Gas exchange; Nitrogen dioxide; Stomatal uptake; Vegetation

Quantitative and enantioselective analysis of monoterpenes from plant chambers and in ambient air using SPME - Yassaa, N.; Custer, T.; Song, W.; Pech, F.; Kesselmeier, J.; Williams, J. (ATMOSPHERIC MEASUREMENT TECHNIQUES, 2010)
A headspace solid-phase microextraction (HS-SPME) and gas chromatography/mass spectrometry (GC/MS) system has been developed for quantifying enantiomeric and nonenantiomeric monoterpenes in plant chamber studies and ambient air. Performance of this system was checked using a capillary diffusion system to produce monoterpene standards. The adsorption efficiency, competitive adsorption and chromatographic peak resolution of monoterpene enantiomer pairs were compared for three SPME fibre coatings: 75 mu m Carboxen-PDMS (CAR-PDMS), 50/30 mu m divinylbenzene-carboxen-polydimethylsiloxane (DVB-CAR-PDMS) and 65 mu m divinylbenzene-polydimethylsiloxane (DVB-PDMS). Key parameters such as the linearity and reproducibility of the SPME system have been investigated in this work. The best compromise between the enantiomeric separation of monoterpenes and competitive adsorption of the isoprenoids on the solid SPME fibre coating was found for DVB-PDMS fibres. The optimum conditions using DVB-PDMS fibres were applied to measure the exchange rates of monoterpenes in the emission of Quercus ilex using a laboratory whole plant enclosure under light and dark conditions, as well as in ambient air. With 592 and 223 ng m(-2) s(-1) respectively, beta-myrcene and limonene were the predominant monoterpenes in the emission of Q. ilex. These values were closely comparable to those obtained using a zNose and cartridge GC-FID systems.
The following values have no corresponding Zotero field: pub-location: BAHNHOFSALLEE 1E, GOTTINGEN, 37081, GERMANY publisher: COPERNICUS GESELLSCHAFT MBH
Keywords: GC/MS; Quercus ilex